Polyurethane foam composite material for purification driven by photo-thermal interface desalination, construction method and application

By adding soluble melanin and dopamine hydrochloride to polyurethane foam, a porous foam structure is generated, which solves the problem of low light absorption and heat conversion efficiency of polyurethane foam composite materials in the field of photothermal interface evaporation. This enables efficient and stable seawater desalination and brackish water purification, is suitable for various water quality conditions, and reduces operating costs.

CN120842528APending Publication Date: 2025-10-28XINJIANG UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511088963.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-05
Publication Date
2025-10-28

AI Technical Summary

Technical Problem

Existing polyurethane foam composite materials have low light absorption capacity and heat conversion efficiency in the field of photothermal interface evaporation, insufficient long-term stability, limited selective adsorption capacity, difficulty in efficiently separating specific salt ions, and unassessed environmental impact.

Method used

By adding soluble melanin and dopamine hydrochloride during the foaming process, a porous foam structure is generated, which improves light absorption capacity and heat conversion efficiency. Furthermore, by optimizing the foaming and curing processes, the stability and selective adsorption capacity of the material are enhanced.

Benefits of technology

It significantly improves the light absorption capacity and heat conversion efficiency of polyurethane foam composite materials, enhances their long-term stability and selective adsorption capacity in complex water quality environments, makes them suitable for various water quality conditions, reduces operating costs and reduces resource waste.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120842528A_ABST
    Figure CN120842528A_ABST
Patent Text Reader

Abstract

The invention relates to a photo-thermal interface desalination-driven polyurethane foam composite material for purification, a construction method and application, and belongs to the field of photo-thermal interface evaporation. According to the method, a polyurethane polymer is generated through an addition polymerization reaction of polyol and polyisocyanate, soluble melanin and dopamine hydrochloride are added in the foaming process, the soluble melanin and the dopamine hydrochloride are uniformly dispersed in foam through an oxidation self-polymerization reaction of the soluble melanin and the dopamine hydrochloride, and the light absorption capacity and the thermal conversion efficiency of the material are remarkably improved. The preparation method comprises the following specific steps: mixing polyether polyol with soluble melanin, adding a catalyst, a foam stabilizer, a foaming agent, dopamine hydrochloride and ammonia water, stirring, adding toluene diisocynate for foaming, and finally curing and curing to obtain the composite material. The invention solves the problems of low light absorption capacity and heat conversion efficiency of the existing polyurethane foam, is suitable for seawater desalination and brackish water purification, has the advantages of high efficiency, low cost, wide application range and the like, and is particularly suitable for being popularized and used in drought regions with sufficient sunlight.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of photothermal interface evaporation, specifically to a photothermal interface desalination-driven polyurethane foam composite material for purification, its construction method, and its application. Background Art

[0002] Water is a fundamental resource for sustaining life and ecosystems on Earth, and a crucial guarantee for driving socio-economic development. However, with the rapid increase in global population and the impact of climate change, water scarcity is becoming increasingly severe. According to UNESCO statistics, approximately 2 billion people worldwide live in severely water-scarce areas, and over 4 billion people face water shortages for at least one month each year. Simultaneously, water pollution caused by accelerated industrialization further exacerbates freshwater scarcity, making corresponding technologies urgently needed to address these issues. Water purification technology is one of the important ways to solve the freshwater shortage problem, mainly including reverse osmosis, electrodialysis multi-stage flash evaporation, groundwater extraction, and rainwater harvesting. However, these traditional water purification technologies consume large amounts of energy and face many challenges in practical application. For example, reverse osmosis and electrodialysis technologies have high operating costs, and their high energy consumption exacerbates carbon emissions, making them difficult to promote in resource-scarce areas. Furthermore, these water purification facilities typically need to be located near coastlines, making them unsuitable for arid inland or remote areas. In addition, excessive groundwater extraction can lead to land subsidence and ecological damage, while the efficiency of rainwater harvesting is limited by climatic conditions, and stored water resources are easily polluted.

[0003] Against this backdrop, researchers have turned their attention to novel polyurethane foam composites. Their high porosity, mechanical stability, chemical durability, lightweight structure, and tunable surface properties make them ideal carriers for new desalination technologies. Furthermore, their reusability after simple processing effectively reduces operating costs and resource waste. Through surface modification or chemical alteration, polyurethane foam composites can selectively adsorb salt ions and impurities from seawater while allowing water molecules to pass through, thus achieving the separation and collection of freshwater and providing a new approach to overcoming the limitations of traditional water desalination technologies. However, polyurethane foam composites still face some challenges in practical applications. Their long-term stability is insufficient, especially in complex water environments, where their performance may decline over time. Their selective adsorption capacity is limited, making it difficult to efficiently separate specific salt ions. The process optimization issues for large-scale applications have not been fully resolved, including controlling production costs and improving equipment design. In addition, the environmental impact of polyurethane foam needs further assessment, such as whether its degradation products pose potential harm to ecosystems. Through continuous optimization of material properties and processing technologies, polyurethane foam composites are expected to achieve large-scale application in unconventional water desalination, providing sustainable freshwater solutions for arid and resource-scarce regions. This will not only help alleviate the water crisis, but will also promote the achievement of global sustainable development goals and lay a solid foundation for the future of human society. Summary of the Invention

[0004] This invention provides a photothermal interface desalination-driven polyurethane foam composite material for purification, its construction method, and its applications. It solves the problems of low light absorption capacity and low thermal conversion efficiency in existing polyurethane foam composite materials. First, a polyurethane polymer is generated through an addition polymerization reaction between a polyol and a polyisocyanate. Simultaneously, soluble melanin, dopamine hydrochloride, and ammonia are added to the foaming system. This causes dopamine hydrochloride to undergo oxidative self-polymerization in the reaction system, and the dopamine hydrochloride, along with the soluble melanin, is uniformly dispersed in the system during the foaming process, improving the light absorption capacity and thermal conversion efficiency of the polyurethane foam. Then, carbon dioxide (CO2) gas is generated by the reaction of water with isocyanate groups. The generated CO2 gas forms bubbles in the reaction system, causing the polymer to expand and solidify, forming a porous foam structure. This enables applications such as seawater desalination and brackish water purification.

[0005] To achieve the above-mentioned objectives, the present invention adopts the following technical solution: In a first aspect, the present invention provides a method for constructing a polyurethane foam composite material for purification driven by photothermal interface desalination, the method comprising the following steps: S1. Add soluble melanin to polyether polyol, with a mass ratio of polyether polyol to soluble melanin of 100:1~5, stir and mix evenly to obtain a mixture; S2. Add the tin-based catalyst, amine catalyst, foam stabilizer, and foaming agent to the mixture from step S1. S3. Add dopamine hydrochloride and ammonia to the mixture from step S2 and stir until well mixed. S4. Add toluene diisocyanate to the mixture being stirred in step S3, and stir until well mixed; S5. Transfer the mixture from step S4 into a mold and place it in an oven for foaming. S6. After foaming, let the product mature in an oven; S7. Remove the product from the oven and cure it to obtain a polyurethane foam composite material for purification driven by photothermal interface desalination.

[0006] Preferably, in step S1 described above, the polyether polyol is polyether polyol HK330N. The polyether polyol neutralizes the soluble melanin and is placed in a reaction vessel. The reaction vessel is then placed on a magnetic stirrer at a speed of 400 rpm for 5 minutes. A beaker can be used as the reaction vessel.

[0007] Preferably, in step S2 described above, the tin catalyst is dibutyltin dilaurate, and the mass ratio of the tin catalyst to the polyether polyol is 11:1000; the amine catalyst is diethylenetriamine, and the mass ratio of the amine catalyst to the polyether polyol is 3:1000; the foam stabilizer is polyether-modified heptamethyltrisiloxane, and the mass ratio of the foam stabilizer to the polyether polyol is 1:40; and the foaming agent is deionized water, and the mass ratio of the foaming agent to the polyether polyol is 1:50.

[0008] Preferably, in step S3 described above, the mass ratio of dopamine hydrochloride to polyether polyol is 0~4:100, and the mass ratio of ammonia to polyether polyol is 1~1.6:100. The mixture is stirred using a magnetic stirrer at a speed of 600 rpm for 5 minutes.

[0009] Preferably, in step S4 described above, the mass ratio of toluene diisocyanate to polyether polyol is 3:10, and the mixture is stirred using a magnetic stirrer. The speed of the magnetic stirrer is increased from 600 rpm in S3 to 1500 rpm, and the mixture is stirred for 1 min.

[0010] Preferably, in step S5 described above, the oven temperature is 25 ℃ and the foaming time is 10 min.

[0011] Preferably, in step S6 described above, the oven temperature is 50 ℃ and the curing time is 2 h.

[0012] Preferably, in step S7 described above, the product is placed in a fume hood for curing for 24 hours to ensure that the oxidative self-polymerization reaction of dopamine hydrochloride is complete.

[0013] Secondly, the present invention provides a photothermal interface desalination-driven purification polyurethane foam composite material prepared according to the manufacturing method described above.

[0014] Thirdly, the present invention provides the application of the above-mentioned photothermal interface desalination-driven polyurethane foam composite material for purification in the fields of seawater desalination, brackish water purification and dyeing wastewater purification.

[0015] Compared with the prior art, the present invention has the following beneficial effects: (1) Improving light absorption capacity and heat conversion efficiency: Existing polyurethane foam composite materials suffer from low light absorption capacity and heat conversion efficiency in the field of photothermal interface evaporation. This invention significantly improves the light absorption capacity and heat conversion efficiency of polyurethane foam composite materials by adding soluble melanin and dopamine hydrochloride during the foaming process and dispersing them uniformly in the polyurethane foam. This enables the composite material to more effectively utilize solar energy for seawater desalination and brackish water purification, thereby improving the purification efficiency of unconventional water resources.

[0016] (2) Applicable to various water quality environments: By adding soluble melanin and dopamine hydrochloride, this invention not only improves light absorption and heat conversion efficiency, but also enhances the selective adsorption capacity of polyurethane foam. This enables the composite material to effectively treat water with different salinity and impurity content, including seawater and brackish water, thus broadening its applicability and overcoming the limitations of traditional water desalination technologies.

[0017] (3) Enhanced stability and durability of polyurethane foam composites: This invention ensures the long-term stability of polyurethane foam composites in complex water environments by optimizing the foaming and curing processes. The oxidative self-polymerization reaction of dopamine hydrochloride further enhances the mechanical properties and chemical durability of the material, enabling it to be reused, reducing resource waste, and lowering operating costs. Attached Figure Description

[0018] Figure 1 This is a polyurethane foam for purification driven by photothermal interface desalination in one embodiment of the present invention; Figure 2 This is a diagram of a polyurethane foam seawater desalination test device for purification, according to one embodiment of the present invention. Figure 3 The change of surface temperature of purified water over time under 1 Sun for polyurethane foam of different thicknesses used for purification. Figure 4The change in the mass of purified water evaporated under 1 Sun for purification polyurethane foam of different thicknesses over time; Figure 5 The variation of the mass of purified water evaporated over time under 1 Sun irradiation in different embodiments of the present invention using polyurethane foam for purification. Figure 6 This invention provides an embodiment of a polyurethane foam for purification that simulates the change in the mass of seawater evaporation over time under 1 Sun irradiation. Figure 7 This invention provides an embodiment of a simulation of the change in the mass of brackish water evaporation over time using polyurethane foam for purification under 1 Sun irradiation. Figure 8 This invention provides an embodiment of a simulation of the change in the evaporation mass of dyeing and printing wastewater over time using polyurethane foam for purification under 1 Sun irradiation. Figure 9 The surface temperature response curve of a purification polyurethane foam under 1 Sun irradiation in one embodiment of the invention; Figure 10 This is an infrared thermal image of a polyurethane foam for purification under dry conditions and irradiated by Sun for the first 6 minutes in one embodiment of the present invention. Figure 11 This is an example of the evaporation mass of polyurethane foam for purification under 1 Sun for 6 hours in a simulation of brackish water. Figure 12 This invention illustrates the evaporation performance of polyurethane foam for purification under 1 Sun, simulating the continuous circulation of brackish water for 6 evaporation cycles. Detailed Implementation

[0019] To make the above-mentioned objects, features, and advantages of the present invention more apparent and understandable, specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings. Many specific details are set forth in the following description to provide a thorough understanding of the present invention. However, the present invention can be practiced in many other ways different from those described herein, and those skilled in the art can make similar modifications without departing from the spirit of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0020] Example 1 This invention provides a method for constructing a polyurethane foam composite material for purification driven by photothermal interface desalination, which includes the following steps: S1. Weigh 10 g of polyether polyol HK330N and 0.1 g of soluble melanin (alcohol-soluble) and add them to a beaker. Then place the beaker on a magnetic stirrer and stir at 400 rpm for 5 min to obtain a mixture. S2. Add 0.11 g of dibutyltin dilaurate (tin catalyst), 0.03 g of diethylenetriamine (amine catalyst), 0.2 g of purified water (foaming agent) and 0.25 g of polyether-modified heptamethyltrisiloxane (foam stabilizer) to the mixture in step S1 in sequence. S3. Weigh 0.1 g of dopamine hydrochloride and 0.1 ml of ammonia water, add them to the mixture in step S2 and place them on a magnetic stirrer. Stir at 600 rpm for 5 min to disperse them evenly in the mixture. S4. Quickly add 3 g of toluene diisocyanate to the mixture being stirred and increase the speed to 1500 rpm, stir for 1 min; S5. Quickly transfer the well-stirred mixture into the mold and place it in a 25°C oven to foam for 10 minutes. S6. After foaming is complete, increase the oven temperature to 50 ℃ and allow the product to mature for 2 hours. S7. Remove the product from the oven and place it in a fume hood for curing for 24 hours to allow the oxidative self-polymerization reaction of dopamine hydrochloride to be completed, thereby obtaining a polyurethane foam composite material for purification driven by photothermal interface desalination.

[0021] Example 2 This invention provides a method for constructing a polyurethane foam composite material for purification driven by photothermal interface desalination, which includes the following steps: S1. Weigh 10 g of polyether polyol HK330N and 0.5 g of soluble melanin (alcohol-soluble) and add them to a beaker. Then place the beaker on a magnetic stirrer and stir at 400 rpm for 5 min to obtain a mixture. S2. Add 0.11 g of dibutyltin dilaurate (tin catalyst), 0.03 g of diethylenetriamine (amine catalyst), 0.2 g of purified water (foaming agent) and 0.25 g of polyether-modified heptamethyltrisiloxane (foam stabilizer) to the mixture in step S1 in sequence. S3. Weigh 0.1 ml of ammonia water, add it to the mixture in step S2, and place it on a magnetic stirrer and stir at 600 rpm for 5 min to make it evenly dispersed in the mixture. S4. Quickly add 3 g of toluene diisocyanate to the mixture being stirred and increase the speed to 1500 rpm, stir for 1 min; S5. Quickly transfer the well-stirred mixture into the mold and place it in a 25°C oven to foam for 10 minutes. S6. After foaming is complete, increase the oven temperature to 50 ℃ and allow the product to mature for 2 hours. S7. Remove the product from the oven and place it in a fume hood for curing for 24 hours to allow the oxidative self-polymerization reaction of dopamine hydrochloride to be completed, thereby obtaining a polyurethane foam composite material for purification driven by photothermal interface desalination.

[0022] Example 3 This invention provides a method for constructing a polyurethane foam composite material for purification driven by photothermal interface desalination, which includes the following steps: S1. Weigh 10 g of polyether polyol HK330N and 0.4 g of soluble melanin (alcohol-soluble) and add them to a beaker. Then place the beaker on a magnetic stirrer and stir at 400 rpm for 5 min to obtain a mixture. S2. Add 0.11 g of dibutyltin dilaurate (tin catalyst), 0.03 g of diethylenetriamine (amine catalyst), 0.2 g of purified water (foaming agent) and 0.25 g of polyether-modified heptamethyltrisiloxane (foam stabilizer) to the mixture in step S1 in sequence. S3. Weigh 0.1 g of dopamine hydrochloride and 0.1 ml of ammonia water, add them to the mixture in step S2, and place them on a magnetic stirrer and stir at 600 rpm for 5 min to make them evenly dispersed in the mixture. S4. Quickly add 3 g of toluene diisocyanate to the mixture being stirred and increase the speed to 1500 rpm, stir for 1 min; S5. Quickly transfer the well-stirred mixture into the mold and place it in a 25°C oven to foam for 10 minutes. S6. After foaming is complete, increase the oven temperature to 50 ℃ and allow the product to mature for 2 hours. S7. Remove the product from the oven and place it in a fume hood for curing for 24 hours to allow the oxidative self-polymerization reaction of dopamine hydrochloride to be completed, thereby obtaining a polyurethane foam composite material for purification driven by photothermal interface desalination.

[0023] Example 4 This invention provides a method for constructing a polyurethane foam composite material for purification driven by photothermal interface desalination, which includes the following steps: S1. Weigh 10 g of polyether polyol HK330N and 0.3 g of soluble melanin (alcohol-soluble) and add them to a beaker. Then place the beaker on a magnetic stirrer and stir at 400 rpm for 5 min to obtain a mixture. S2. Add 0.11g dibutyltin dilaurate (tin catalyst), 0.03g diethylenetriamine (amine catalyst), 0.2g purified water (foaming agent), and 0.25g polyether-modified heptamethyltrisiloxane (foam stabilizer) sequentially to the mixture from step S1. S3. Weigh 0.2 g of dopamine hydrochloride and 0.1 ml of ammonia water, add them to the mixture in step S2, and place them on a magnetic stirrer and stir at 600 rpm for 5 min to make them evenly dispersed in the mixture. S4. Quickly add 3 g of toluene diisocyanate to the mixture being stirred and increase the speed to 1500 rpm, stir for 1 min; S5. Quickly transfer the well-stirred mixture into the mold and place it in a 25°C oven to foam for 10 minutes. S6. After foaming is complete, increase the oven temperature to 50 ℃ and allow the product to mature for 2 hours. S7. Remove the product from the oven and place it in a fume hood for curing for 24 hours to allow the oxidative self-polymerization reaction of dopamine hydrochloride to be completed, thereby obtaining a polyurethane foam composite material for purification driven by photothermal interface desalination.

[0024] Example 5 This invention provides a method for constructing a polyurethane foam composite material for purification driven by photothermal interface desalination, which includes the following steps: S1. Weigh 10 g of polyether polyol HK330N and 0.2 g of soluble melanin (alcohol-soluble) and add them to a beaker. Then place the beaker on a magnetic stirrer and stir at 400 rpm for 5 min to obtain a mixture. S2. Add 0.11 g of dibutyltin dilaurate (tin catalyst), 0.03 g of diethylenetriamine (amine catalyst), 0.2 g of purified water (foaming agent) and 0.25 g of polyether-modified heptamethyltrisiloxane (foam stabilizer) to the mixture in step S1 in sequence. S3. Weigh 0.3 g of dopamine hydrochloride and 0.1 ml of ammonia water, add them to the mixture in step S2, and place them on a magnetic stirrer and stir at 600 rpm for 5 min to make them evenly dispersed in the mixture. S4. Quickly add 3 g of toluene diisocyanate to the mixture being stirred and increase the speed to 1500 rpm, stir for 1 min; S5. Quickly transfer the well-stirred mixture into the mold and place it in a 25°C oven to foam for 10 minutes. S6. After foaming is complete, increase the oven temperature to 50 ℃ and allow the product to mature for 2 hours. S7. Remove the product from the oven and place it in a fume hood for curing for 24 hours to allow the oxidative self-polymerization reaction of dopamine hydrochloride to be completed, thereby obtaining a polyurethane foam composite material for purification driven by photothermal interface desalination.

[0025] Example 6 This invention provides a method for constructing a polyurethane foam composite material for purification driven by photothermal interface desalination, which includes the following steps: S1. Weigh 10 g of polyether polyol HK330N and 0.1 g of soluble melanin (alcohol-soluble) and add them to a beaker. Then place the beaker on a magnetic stirrer and stir at 400 rpm for 5 min to obtain a mixture. S2. Add 0.11 g of dibutyltin dilaurate (tin catalyst), 0.03 g of diethylenetriamine (amine catalyst), 0.2 g of purified water (foaming agent) and 0.25 g of polyether-modified heptamethyltrisiloxane (foam stabilizer) to the mixture in step S1 in sequence. S3. Weigh 0.4 g of dopamine hydrochloride and 0.1 ml of ammonia water, add them to the mixture in step S2, and place them on a magnetic stirrer and stir at 600 rpm for 5 min to make them evenly dispersed in the mixture. S4. Quickly add 3 g of toluene diisocyanate to the mixture being stirred and increase the speed to 1500 rpm, stir for 1 min; S5. Quickly transfer the well-stirred mixture into the mold and place it in a 25°C oven to foam for 10 minutes. S6. After foaming is complete, increase the oven temperature to 50 ℃ and allow the product to mature for 2 hours. S7. Remove the product from the oven and place it in a fume hood for curing for 24 hours to allow the oxidative self-polymerization reaction of dopamine hydrochloride to be completed, thereby obtaining a polyurethane foam composite material for purification driven by photothermal interface desalination.

[0026] Example 7 This invention provides a method for constructing a polyurethane foam composite material for purification driven by photothermal interface desalination, which includes the following steps: S1. Weigh 10 g of polyether polyol HK330N and add it to a beaker. Then place the beaker on a magnetic stirrer and stir at 400 rpm for 5 min to obtain a mixture. S2. Add 0.11 g of dibutyltin dilaurate (tin catalyst), 0.03 g of diethylenetriamine (amine catalyst), 0.2 g of purified water (foaming agent) and 0.25 g of polyether-modified heptamethyltrisiloxane (foam stabilizer) to the mixture in step S1 in sequence. S3. Weigh 0.5 g of dopamine hydrochloride and 0.1 ml of ammonia water, add them to the mixture in step S2, and place them on a magnetic stirrer and stir at 600 rpm for 5 min to make them evenly dispersed in the mixture. S4. Quickly add 3 g of toluene diisocyanate to the mixture being stirred and increase the speed to 1500 rpm, stir for 1 min; S5. Quickly transfer the well-stirred mixture into the mold and place it in a 25°C oven to foam for 10 minutes. S6. After foaming is complete, increase the oven temperature to 50 ℃ and allow the product to mature for 2 hours. S7. Remove the product from the oven and place it in a fume hood for curing for 24 hours to allow the oxidative self-polymerization reaction of dopamine hydrochloride to be completed, thereby obtaining a polyurethane foam composite material for purification driven by photothermal interface desalination.

[0027] In the above embodiments, since dopamine hydrochloride is added in step S3, melanin is added in step S1 instead of in step S1. That is, dopamine hydrochloride and melanin are added in two separate steps instead of in the same step. As the core material for photothermal conversion, melanin needs to be fully dispersed in the polyether polyol matrix. If it is added at the same time as dopamine hydrochloride, the two may agglomerate due to intermolecular forces (such as π-π stacking or hydrogen bonding), which will reduce the dispersion uniformity and affect the photothermal performance.

[0028] Examples 1-7 selected melanin as the photothermal component. After absorbing light energy, melanin generates heat through non-radiative relaxation, which is concentrated on the material surface and pore interface, forming a localized high-temperature zone, thus converting light energy into heat energy. PDA (polydopamine), generated by the self-polymerization of dopamine hydrochloride, covers the interior of the pores, promoting capillary water transport and enhancing resistance to salt crystallization fouling. Furthermore, the spatially separated distribution of melanin and PDA avoids spectral competition for absorption, maximizing light utilization efficiency.

[0029] In the photothermal interface desalination-driven purification polyurethane foam, melanin and dopamine hydrochloride are added stepwise to avoid aggregation and competitive reactions. Dopamine hydrochloride self-polymerizes to form PDA after foaming, preventing structural damage during the foaming process and improving coating integrity. The polyurethane matrix (HK330N, toluene diisocyanate, etc.) is a commonly used industrial raw material; melanin and dopamine hydrochloride are inexpensive and non-toxic; and PDA is biodegradable, releasing no harmful substances after use, demonstrating environmental friendliness. The polyurethane foam combines high water flux and mechanical elasticity. Melanin is enriched on the foam skeleton surface, maximizing light absorption and heat conversion. PDA coating the pores forms superhydrophilic channels (contact angle <10°), rapidly transporting water through capillary action, preventing the evaporation interface from drying out, thereby further improving evaporation efficiency.

[0030] The photothermal interface desalination-driven polyurethane foam preparation process and materials in the above embodiments have low cost, simple preparation process, zero external energy dependence, and wide applicability, and can be used for water purification in various environments.

[0031] Table 1 is a summary table of the quality of materials added in Examples 1-7; Example Polyether polyol HK330N (g) Dibutyltin dilaurate (g) Diethylenetriamine (g) Purified water (ml) Polyether-modified heptamethyltrisiloxane (g) Soluble melanin (g) Dopamine hydrochloride (g) Ammonia water (ml) Toluene diisocyanate (g) 1 10 0.11 0.03 0.2 0.25 0.1 0.1 0.1 3 2 10 0.11 0.03 0.2 0.25 0.5 0 0.1 3 3 10 0.11 0.03 0.2 0.25 0.4 0.1 0.1 3 4 10 0.11 0.03 0.2 0.25 0.3 0.2 0.1 3 5 10 0.11 0.03 0.2 0.25 0.2 0.3 0.1 3 6 10 0.11 0.03 0.2 0.25 0.1 0.4 0.1 3 7 10 0.11 0.03 0.2 0.25 0 0.5 0.1 3 It should be noted that the steps in Examples 1-7 are basically the same, except that the content of soluble melanin and dopamine hydrochloride in the prepared polyurethane foam is different. Example 1 explored whether the foam could be molded, while in Examples 2-7, the total amount of soluble melanin and dopamine hydrochloride was 0.5 g, investigating the effect of the content of these two substances on the photothermal rate. The foam in Example 7 experienced solidification during molding, so only Examples 1-6 were tested for photothermal performance and evaporation performance. The photothermal interface evaporation device showed the best evaporation efficiency when the sponge thickness was 1 cm. The testing process of the product from Example 3 will be described below as an example.

[0032] I. Construction of the photothermal interface evaporation device, see [link / reference]. Figures 1-2 The prepared polyurethane foam was cut into a block with a front surface size of 2 x 2 cm and a height of 1 cm, as shown below. Figure 1 As shown.

[0033] from Figure 2 As can be seen, the photothermal interface device consists of three parts: a simulated light source, an evaporation device, and an electronic balance. A xenon lamp is used to simulate sunlight, and a power meter is used to test the irradiance. In the experiment of evaporating pure water, the electronic balance is used for continuous weighing to accurately measure the mass change. By analyzing the data, the evaporation rate of the product can be calculated. An insulation layer needs to be added to the evaporation device to avoid excessive contact between the photothermal evaporation interface and the water, thus minimizing heat loss through conduction. However, to simulate a real-world application scenario, no insulation layer was added in the following tests and simulations.

[0034] II. For the evaporation performance of the photothermal interface evaporator on pure water, please refer to... Figures 3-9 The schematic diagram of the photothermal interface evaporation device clearly demonstrates the seawater desalination test process without the need for an insulation layer covering the water surface. A 1 cm thick layer of purification polyurethane foam was placed under one solar intensity condition for testing, and the changes in the quality and temperature of the purified water over time were observed. Figure 3 , 4 As shown. Figure 4 As shown, the evaporation rate of 1 cm thick polyurethane foam used for purification is as high as 2.35 kg·m³. -2 ·h -1 It is pure water (0.48 kg·m³). -2 ·h -1 4.1 times that of ).

[0035] like Figure 3 As shown, infrared thermal imaging revealed that the surface temperature of a 1 cm thick photothermal interface evaporation device during water evaporation was 40.6 °C, higher than the 30.7 °C for a 0.5 cm thick device and the 36.5 °C for a 1.25 cm thick device. This phenomenon may be due to the substrate absorbing too much moisture, thus failing to effectively increase the temperature of the evaporation interface, or the insufficient distance between the surface of the polyurethane composite material and the liquid surface, resulting in ineffective heat transfer.

[0036] like Figure 5 As shown, by investigating the change in the mass of purified water evaporated over time under 1 Sun irradiation using polyurethane foams for purification in Experiments 1-6, the polyurethane foam with the best photothermal performance was selected. Among them, the polyurethane foam in Experiment 3 had the best photothermal performance, with an evaporation rate of purified water as high as 2.35 kg·m³. -2 ·h -1 .

[0037] like Figures 6-8 The figures show the simulated photothermal evaporation tests of seawater, brackish water, and dyeing wastewater in the optimal experimental example 3, respectively. These data clearly demonstrate the excellent photothermal evaporation performance of the polyurethane composite material under different water quality conditions. Whether in the high-salinity simulated seawater environment or in the complex simulated brackish water and dyeing wastewater, the polyurethane composite material maintains a high efficiency in photothermal conversion. This superior performance indicates the wide applicability of the polyurethane composite material, effectively addressing various complex water purification scenarios and fully demonstrating its universality and stability under different water quality conditions.

[0038] like Figure 9The photothermal evaporation device exhibits significant thermal response characteristics under enhanced radiation conditions. When the xenon lamp irradiation intensity increases, the surface temperature of the material shows a stable upward trend; after irradiation stops, it enters a rapid cooling phase. This sensitive temperature change following irradiation on / off cycles verifies the material's excellent thermal dynamic characteristics. Under standard solar irradiation intensity, the surface temperature of the device exhibits a two-stage change: a rapid rise to 65°C within the first 120 seconds, followed by a slow rise to 70°C within the next 300 seconds. This confirms that the modified polyurethane matrix possesses both rapid thermal response and long-term thermal stability. By precisely controlling the nano-absorbing layer and microchannel heat conduction network of the foam matrix, a synergistic effect of broad-spectrum solar absorption and efficient local thermal energy retention is achieved. Its thermodynamic characteristics directly accelerate the water molecule phase transition process, resulting in an order-of-magnitude increase in evaporation flux. The transient thermal surge and steady-state heat output characteristics exhibited by this material system provide an innovative solution for overcoming the energy efficiency bottleneck of traditional interfacial evaporation technology. In particular, the short-term rapid temperature rise characteristics exhibited in the temperature response curve are significantly better than those of polyurethane foam photothermal material systems reported in existing literature, laying a material foundation for the development of a new generation of high-efficiency seawater desalination devices.

[0039] Figure 11 and Figure 12 To evaluate the continuous evaporation capacity of the photothermal interface evaporation device, a 6-hour continuous brackish water evaporation experiment was conducted under one solar intensity condition, and the sample was irradiated for six cycles. Neither experiment showed a significant decrease in evaporation rate. Therefore, the photothermal interface evaporation device possesses stable evaporation capacity and can be widely applied in unconventional water desalination.

[0040] All reagents used in this embodiment are of analytical grade.

[0041] Furthermore, it should be understood that the above-described embodiments are only used to explain the present invention in detail, but the present invention is not limited to the detailed methods described above. For those skilled in the art, any improvements to the present invention, equivalent substitutions of raw materials for the products of the present invention, selection of specific methods, etc., within the spirit and principles of the present invention, should be covered within the scope of protection and disclosure of the present invention.

Claims

1. A method for constructing a polyurethane foam composite material for purification driven by photothermal interface desalination, characterized in that, Includes the following steps: S1. Add soluble melanin to polyether polyol, with a mass ratio of polyether polyol to soluble melanin of 100:1~5, stir and mix evenly to obtain a mixture; S2. Add the tin-based catalyst, amine catalyst, foam stabilizer, and foaming agent to the mixture from step S1. S3. Add dopamine hydrochloride and ammonia to the mixture from step S2 and stir until well mixed. S4. Add toluene diisocyanate to the mixture being stirred in step S3, and stir until well mixed; S5. Transfer the mixture from step S4 into a mold and place it in an oven for foaming. S6. After foaming, let the product mature in an oven; S7. Remove the product from the oven and cure it to obtain a polyurethane foam composite material for purification driven by photothermal interface desalination.

2. The method for constructing a polyurethane foam composite material for purification driven by photothermal interface desalination according to claim 1, characterized in that: In step S1, the polyether polyol is polyether polyol HK330N; in step S1, a magnetic stirrer is used for stirring and mixing at a speed of 400 rpm for 5 min.

3. The method for constructing a polyurethane foam composite material for purification driven by photothermal interface desalination according to claim 1, characterized in that: In step S2, the tin catalyst is dibutyltin dilaurate, and the mass ratio of the tin catalyst to the polyether polyol is 11:1000; the amine catalyst is diethylenetriamine, and the mass ratio of the amine catalyst to the polyether polyol is 3:1000; the foam stabilizer is polyether-modified heptamethyltrisiloxane, and the mass ratio of the foam stabilizer to the polyether polyol is 1:40; and the foaming agent is deionized water, and the mass ratio of the foaming agent to the polyether polyol is 1:

50.

4. The method for constructing a polyurethane foam composite material for purification driven by photothermal interface desalination according to claim 1, characterized in that: In step S3, the mass ratio of dopamine hydrochloride to polyether polyol is 0~4:100, and the mass ratio of ammonia to polyether polyol is 1~1.6:

100. The reaction vessel is placed on a magnetic stirrer and stirred and mixed using a magnetic stirrer at a speed of 600 rpm for 5 min.

5. The method for constructing a polyurethane foam composite material for purification driven by photothermal interface desalination according to claim 1, characterized in that: In step S4, the mass ratio of toluene diisocyanate to polyether polyol is 3:10, and the mixture is stirred using a magnetic stirrer with the speed increased to 1500 rpm for 1 min.

6. The method for constructing a polyurethane foam composite material for purification driven by photothermal interface desalination according to claim 1, characterized in that: In step S5, the oven temperature is 25 ℃ and the foaming time is 10 min.

7. The method for constructing a polyurethane foam composite material for purification driven by photothermal interface desalination according to claim 1, characterized in that: In step S6, the oven temperature is 50 ℃ and the curing time is 2 h.

8. The method for constructing a polyurethane foam composite material for purification driven by photothermal interface desalination according to claim 1, characterized in that: In step S7, the product is placed in a fume hood for curing for 24 hours to ensure that the oxidative self-polymerization reaction of dopamine hydrochloride is complete.

9. A polyurethane foam composite material for purification driven by photothermal interface desalination, characterized in that, A polyurethane foam composite material prepared by any one of claims 1 to 8.

10. The application of the photothermal interface desalination-driven polyurethane foam composite material for purification as described in claim 9 in the fields of seawater desalination, brackish water purification, and dyeing wastewater purification.